2016
DOI: 10.17706/ijeeee.2016.6.1.27-39
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Business Model for Online Education Resources and e-Learning Implementation in a Developing Country: Case of Tanzania

Abstract: This paper presents a business model for the ICT in education projects implementation. Using a design-research approach, we analyzed cases of the Online Resources and eLearning Implementation (OREI) framework that we developed. After the theoretical background, we discussed the proposed framework and a set of steps to guide the implementation. We formulated the framework practices and the levels of implementation precedencies using Matlab tools, and used Unified Modeling Language (UML) artifacts to present a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…TPACK helps to contextualise the teacher knowledge required for technology integration. SAMR assists in analysing the specific levels used for enhancement and transformation and presents an opportunity to examine the integration from both the teachers' and students' perspectives (Kihoza et al, 2016). The classroom challenge is that learners are now digital and the fact that they are beyond technology-savvy while many teachers are digital immigrants.…”
Section: Technology-enhance Active Language Learning: Combining the E...mentioning
confidence: 99%
“…TPACK helps to contextualise the teacher knowledge required for technology integration. SAMR assists in analysing the specific levels used for enhancement and transformation and presents an opportunity to examine the integration from both the teachers' and students' perspectives (Kihoza et al, 2016). The classroom challenge is that learners are now digital and the fact that they are beyond technology-savvy while many teachers are digital immigrants.…”
Section: Technology-enhance Active Language Learning: Combining the E...mentioning
confidence: 99%
“…A study by Ngeze [10] has found, for example, that an unreliable network was one of the key challenges that hindered the use of a learning management system at the University of Dodoma. Other identified challenges have been related to students' negative attitudes toward technology-based learning [10], inadequate computer literacy skills among students and staff [8], [11], [12], [13], and inappropriate curricula for distance learning [6].…”
Section: Introductionmentioning
confidence: 99%
“…Percebe-se que a indisponibilidade de Internet e de equipamentos reduziu a motivação dos professores para incorporar as tecnologias aos objetivos de aprendizagem, o que corrobora estudos anteriores (HERNANDEZ-DE-MENENDEZ; MORALES-MENENDEZ, 2019;HEINONEN et al, 2019;LEPP;REMMIK;PEDASTE, 2017;KIHOZA et al, 2016;LÓPEZ-BELMONTE et al, 2019). "penso que a principal dificuldade deste metodologia em minha prática docente consiste em motivar os estudantes à estudarem fora da sala de aula, isso é cada vez mais difícil, ainda mais quando os estudantes têm muitas atividades como trabalho, filhos, etc" (P16, sexo masculino)…”
Section: Implicações Do Programa Na Prática Pedagógicaunclassified
“…REMMIK ;PEDASTE, 2017;KIHOZA et al, 2016). Apesar disso, alguns docentes os aplicaram durante a formação e alguns declararam estar motivados a adicioná-los futuramente, como comprova a seguinte fala: "Apesar disso tudo me sinto animado para testar essas ferramentas em minhas turmas" (P16, sexo masculino).…”
Section: Implicações Do Programa Na Prática Pedagógicaunclassified
See 1 more Smart Citation